2018
DOI: 10.56093/ijans.v88i3.78281
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and anthelmintic properties of rhizome extracts of Hedychium spicatum

Abstract: Hedychium spicatum (Zingiberaceae) is an ayurvedic traditional medicinal plant known as Spiked Ginger Lily (English) (Anonymous 1994). It is a perennial rhizomatous herb, commonly found in subtropical Himalayan region. The plant is about 1 m tall with fleshy aromatic rhizomes and elongated stem with broadly lanceolate leaves and has different developmental stages of flowering and fruiting (Kirtikar and Basu 1999). The rhizome of the plant contains medicinal properties like antioxidant, antimicrobial, anthelmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The methanolic extract of leaves of Hedychium coronarium (from the Lake Gardens of Kuala Lumpur, Malaysia) were used for the study. The methanolic extract obtained from rhizomes of Hedychium spicatum was found to have potent antioxidant activity [ 71 , 73 , 76 ]. The total phenolic content was estimated using the gallic acid calibration equation y = 0.0111 × 0.0148 (R 2 = 0.9998), and the total phenolic content of Hedychium coronarium was 820 ± 55 mg GAE/100 g, with significance of p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methanolic extract of leaves of Hedychium coronarium (from the Lake Gardens of Kuala Lumpur, Malaysia) were used for the study. The methanolic extract obtained from rhizomes of Hedychium spicatum was found to have potent antioxidant activity [ 71 , 73 , 76 ]. The total phenolic content was estimated using the gallic acid calibration equation y = 0.0111 × 0.0148 (R 2 = 0.9998), and the total phenolic content of Hedychium coronarium was 820 ± 55 mg GAE/100 g, with significance of p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous, hydro-ethanolic, hydro-methanolic, and methanol extract were evaluated for activity; the study found that methanolic extract of Hedychium spicatum was as effective as Thiabendazole at 2%, 4%, and 6% concentrations [ 76 ].…”
Section: Methodsmentioning
confidence: 99%